Hemispheric Asymmetry of the Polar Ionospheric Density Investigated by ESR and JVD Radar Observations and TIEGCM Simulations for the Solar Minimum Period. Issue 2 (3rd February 2023) - Kim, E.; Jee, G.; Wang, W.; Kwak, Y.‐S.; Shim, J.‐S.; Ham, Y.‐B.; Kim, Y. H.
Abstract: The ionospheric density displays hemispheric asymmetries in the polar region due to various hemispheric differences, for example, in the offset between geographic and geomagnetic poles and in the geomagnetic field strength. Using ground‐based ionospheric measurements from Vertical Incidence Pulsed Ionospheric Radar with Dynasonde analysis at Jang Bogo Station (JBS), Antarctica and from EISCAT Svalbard Radar (ESR) where both sites are located mostly in the polar cap, we investigate the hemispheric differences in the ionospheric density between the northern and southern hemispheres for geomagnetically quiet and solar minimum condition. The results are also compared with Thermosphere Ionosphere Electrodynamic Global Circulation Model (TIEGCM) simulations. The observations show larger density and stronger diurnal and seasonal variations at JBS in the southern hemisphere than at Svalbard in the northern hemisphere. The diurnal variations of the density peak height are also observed to be much larger at JBS. In both hemispheres, the ionospheric density is significantly reduced in winter due to the limited solar production at high geographic latitudes, but TIEGCM considerably overestimates winter density, which is even larger than summer density, especially in the northern hemisphere. Also existed are the differences in the equinoctial asymmetry between the observations and the simulations: the daytime F‐region density is observed to be larger in fall than in spring in both hemispheres, but TIEGCM shows the opposite. In general, most of the observed asymmetrical density are much weaker in the model simulation, which may result from lack of proper magnetospheric forcings and neutral dynamics in the model. Plain Language Summary: The global ionospheric density is not symmetric around the equator due to various reasons. The main reason for the asymmetry would be the asymmetric characteristics of the geomagnetic field. The ionospheric plasma motions are strongly controlled by the magnetic field lines and the magnetospheric energy inputs dominate the polar ionosphere. Therefore, the asymmetric geometry of the magnetic field lines and the offset between the geomagnetic and geographic poles can produce asymmetric density distributions of the ionosphere. However, the investigation of the hemispheric asymmetry has been mostly restricted to the low and mid‐latitude ionosphere and little study has been conducted in the polar ionosphere, mainly due to the lack of observations in the southern hemisphere. Since the establishment of the Jang Bogo Station (JBS), Antarctica in 2014, Korea Polar Research Institute (KOPRI) has been operating various instruments to observe the ionosphere in association with the thermosphere and the magnetosphere. These observations allow us to investigate the hemispheric asymmetry of the ionospheric density by comparing with the observations in the northern polar region. It is found that the diurnal and seasonal variations of the ionospheric density are much stronger at JBS in the southern hemisphere than in Svalbard in the northern hemisphere. Key Points: The polar ionospheric density shows larger magnitude and stronger diurnal and seasonal variations at Jang Bogo Station than in Svalbard The daytime density shows an equinoctial asymmetry which is larger in fall equinox than in spring equinox Thermosphere Ionosphere Electrodynamic Global Circulation Model significantly overestimates the winter density at high latitudes and shows the opposite equinoctial asymmetry to the observations